2015
DOI: 10.1002/eji.201545493
|View full text |Cite
|
Sign up to set email alerts
|

Versatile myeloid cell subsets contribute to tuberculosis‐associated inflammation

Abstract: Tuberculosis (TB), a chronic bacterial infectious disease caused by IntroductionMycobacterium tuberculosis (Mtb) continues to kill more individuals on this globe than any other bacterial contagious agent [1]. A breakthrough in disease pathogenesis was achieved by Robert Koch (1843Koch ( -1910 in 1882, who precisely elucidated the etiology of the disease tuberculosis (TB) [2,3]. Since then, nearly 1 billion deaths have been caused by TB, a higher mortality than any other infectious disease or war in our history… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 157 publications
(205 reference statements)
0
64
0
1
Order By: Relevance
“…9,31 The neutrophil S100A9 protein may be involved in the initial steps of granuloma formation, including the recruitment of peripheral blood neutrophils to the site of inflammation. The S100A9-mediated pathway leading to the transendothelial migration of neutrophils has recently been elucidated at the molecular level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,31 The neutrophil S100A9 protein may be involved in the initial steps of granuloma formation, including the recruitment of peripheral blood neutrophils to the site of inflammation. The S100A9-mediated pathway leading to the transendothelial migration of neutrophils has recently been elucidated at the molecular level.…”
Section: Discussionmentioning
confidence: 99%
“…4,[8][9][10] Of these, neutrophils are the most common and prominently detected cell type in granulomas 9,10 ; however, due to their various functions, which are known to be executed in acute, rather than chronic inflammation, the contribution of neutrophils to the formation of granulomas has not yet been elucidated in detail. In the present study, we found that neutrophils expressing the marker protein, S100A9, accumulated in the central part of granulomas generated in vivo in the bacille Calmette-Guérin (BCG)-challenged guinea pig lung.…”
mentioning
confidence: 99%
“…Mtb interacts with multiple cell types [12,13] and triggers complex tissue changes [14]. Versatility of Mtb regarding its subcellular niches and its facultative intracellular replication correlates with an intricate pathology picture.…”
Section: Mtb and Its Subcellular And Lung Compartmentalizationmentioning
confidence: 99%
“…The diversity of myeloid cell types and subtypes hosting bacilli is increasingly acknowledged [12]. However, vast information on subcellular locations of Mtb emerges from ex vivo studies with macrophages.…”
Section: Mtb and Its Subcellular And Lung Compartmentalizationmentioning
confidence: 99%
“…Mtb, an obligate aerobic intracellular pathogen, gains entry into its host through the respiratory route via aerosols generated by an infected individual. Once inside the pulmonary alveoli, the pathogen is entrapped by alveolar macrophages, neutrophils, dendritic cells (DCs) or even epithelial cells [1,2]. Various ligands present on the mycobacterial cell surface such as phosphatidylinositol mannoside (PIM), HSP70, 19 kDa lipoprotein, lipoarabinomannan (LAM) are recognised by phagocytic receptors and/or specific pattern recognition receptors (PRRs) present at the cell membrane of macrophages or DCs [3].…”
Section: Mycobacterium Tuberculosismentioning
confidence: 99%